Math, asked by SanaMuskaan, 1 month ago

Use Euclid's division algorithm to show that the cube of any positive
integer is of the form 4m or 4m +1 or 4m +3.​

Answers

Answered by tennetiraj86
4

Step-by-step explanation:

Given:-

Cube of a positive integer

To find:-

Use Euclid's division algorithm to show that the cube of any positive integer is of the form 4m or 4m +1 or 4m +3.

Solution:-

We know that

For two positive integers a and b, then there exist unique integers q and r which satisfying a = bq + r where 0 ≤ r < b.

Let a = 4q+r, 0≤r<4

The possible values of r = 0,1,2,3

Case-1:-

If r = 0 then a= 4q+0

=> a = 4q

On cubing both sides then

=> a^3 = (4q)^3

=> a^3 = 64q^3

=> a^3 = 4(16q^3)

=> a^3 = 4m ------------(1)

(Where m = 16q^3)

Case -2:-

If r = 1 then a = 4q+1

On cubing both sides then

=> a^3 = (4q+1)^3

We know that

(a+b)^3 = a^3+3a^2b+3ab^2+b^3

=> a^3 = (4q)^3+3(4q)^2(1)+3(4q)(1)^2+(1)^3

=> a^3 = 64q^3+3(16q^2)+12q+1

=> a^3 = 64q^3+48q^2+12q+1

=>a^3= 4(16q^3+12q^2+3q)+1

=>a^3=4m+1 ---------------(2)

Where, m = 16q^3+12q^2+3q

Case -3:-

If r = 2 then a = 4q+2

on cubing both sides then

=> a^3 = (4q+2)^3

We know that

(a+b)^3 = a^3+3a^2b+3ab^2+b^3

=> a^3 = (4q)^3+3(4q)^2(2)+3(4q)(2)^2+2^3

=>a^3 = 64q^3+3(16q^2)(2)+3(4q)(4)+8

=>a^3 = 64q^3+96q^2+48q+8

=>a^3 = 4(16q^3+24q^2+12q+2)

=>a^3 = 4m ------------------(3)

Where m = 16q^3+24q^2+12q+2

Case -4:-

If r = 3 then a = 4q+3

On cubing both sides then

=> a^3 = (4q+3)^3

We know that

(a+b)^3 = a^3+3a^2b+3ab^2+b^3

=> a^3 = (4q)^3+3(4q)^2(3)+3(4q)(3)^2+(3)^3

=>a^3 = 64q^3+3(16q^2)(3)+3(4q)(9)+27

=>a^3 = 64q^3+144q^2+108q+27

=>a^3 = 64q^3+144q^2+108q+24+3

=>a^3 = 4(16q^3+32q^2+27q+6)+3

=>a^3 = 4m+3----------------(4)

Where, m = 16q^3+32q^2+27q+6

From above all equations

We conclude that

"The cube of any positive integer is in the form of either 4m or 4m+1 or 4m+3"

Hence, Proved.

Used formulae:-

Euclid's Division Lemma:-

For two positive integers a and b, then there exist unique integers q and r which satisfying

a = bq + r where 0 ≤ r < b.

  • (a+b)^3 = a^3+3a^2b+3ab^2+b^3
Answered by rudrarb2403
0

This is a answer........... .......

Attachments:
Similar questions